Desenvolvimento de métodos de preparo de amostras para a posterior determinação de metais alcalinos, alcalino-terrosos e halogênios em petróleo - Nascimento, Mariele Samuel do (2020)
In this work, four sample preparation methods were investigated for further alkaline, alkaline earth metals and halogens determination in crude oil: i ) microwave assisted wet digestion using a pressurized digestion cavity (MAWD PDC), ii ), ultrasound assisted extraction (USAE), iii ) microwave assisted extraction (MAE) and iv ) reversed phase dispersive liquid liquid microextraction (RP DLLME). The results obtained after microwave assisted wet digestion (MAWD) and micr owave induced combustion (MIC) were used as reference values for developed methods (for metals and halogen determination, respectively). Additionally, two standard methods proposed by the American Society for Testing and Materials (ASTM D 5863 and D 6470, for metals and Cl, respectively) were applied. M etals determination was performed by using inductively coupled plasma optical emission spectrometry (ICP OES), the F was determined by ion chromatography (IC) and potentiometry using ion selective electrode ISE), the Cl was determined by inductively coupled plasma mass spectrometry (ICP MS), IC and by potentiometric titration, Br and I were determined by ICP MS. The methods were applied to five crude oil samples, which contained different physical and chemica l properties: API gravity (9.5 a 28.8), water content (0.2 a 79.9%) and sediment content (< 0.1 a 2.8%). Concerning USAE, independent of the experimental conditions used, it was observed that this method was not suitable for the separation of water emulsif ied in crude oil making unfeasible the determination of the elements. The MAWD PDC method showed a good performance for the decomposition of 1.2 g of heavy and medium crude oils using 8 mL of concentrated HNO 3 and 20 min of heating at 270 ºC. However, as e xpected, this method was only suitable for the subsequent determination of metals. In addition, a study related to the effect of carbon concentration (for ICP OES) on the determination of alkaline and alkaline earth metals was performed with digests contai ning 4 g L 1 of carbon from a digest obtained after the MAWD PDC. After the investigation, no interference was observed for any of the investigated elements. The MAE method was applied for the determination of alkaline and alkaline earth metals, as well as for Cl, Br and I in medium and heavy crude oil using 10 g of sample, 15 mL of water as extraction medium and 20 min of heating at 240 ºC. Using MAE, concordances greater than 90% were obtained compared to the reference values. The use of RP DLLME allowed the extraction of alkaline, alkaline earth metals (except Ba), Cl and Br in medium crude oil using only 0.5 mol L 1 HNO 3 . The MAE and RP DLLME methods allowed the use of a high sample mass (10 g), providing LOQs very low, in comparison with the MAWD PDC me thod, for example. In view of the applicability of the developed sample preparation methods, it is important to emphasize that the choice for each of them was dependent directly on intrinsic factors to each crude oil (API gravity sediment content and water content, for example), the elements to be determined, the analytical frequency and the instrumentation available in each laboratory.